2021
DOI: 10.3390/nu13113710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Controlling a Nutritional Status Score on Wound Healing in Patients with Chronic Limb-Threatening Ischemia after Endovascular Treatment

Abstract: Background: Chronic limb-threatening ischemia (CLTI) is the most advanced stage of peripheral artery disease. Therefore, a multidisciplinary approach is necessary to avoid major amputation in CLTI patients. Malnutrition worsens the condition of CLTI patients, and therefore, it may be important to evaluate the nutritional status in patients with CLTI. This study was designed to evaluate the baseline patient characteristics and the influence of the controlling nutritional status (CONUT) score on the clinical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Due to the complexity of earlier PNIs in clinical practice, Onodera’s calculation method, based on peripheral blood lymphocyte counts and serum ALB levels, became simpler 19. Several studies have demonstrated a clear association between PNI and atherosclerotic disease 17 20 21. However, the majority of these studies have been performed in the general population or in those at high risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of earlier PNIs in clinical practice, Onodera’s calculation method, based on peripheral blood lymphocyte counts and serum ALB levels, became simpler 19. Several studies have demonstrated a clear association between PNI and atherosclerotic disease 17 20 21. However, the majority of these studies have been performed in the general population or in those at high risk of CVD.…”
Section: Discussionmentioning
confidence: 99%